TechOne: Automotive Heating and Air Conditioning (sách photo) - Carrigan Russell (Thomson Delmar Learning, 2006)
Automotive heating and air conditioning systems have undergone massive changes in both system design and components as a result of growing concerns for the environment, varying consumer preferences, and industry changes. TechOne: Automotive Heating and Air Conditioning is a modular, performance-based approach to understanding, diagnosing, and repairing automotive-air conditioning systems. It examines the theory behind the operation of the latest generation of heating and air-conditioning systems, including how the theories are applied, and offers readers the opportunity to practice the skills that will enable them to compete in the air-conditioning service market. Material is developed in accordance with NATEF guidelines and takes into account all the criteria needed to adequately prepare readers for the ASE Heating and Air Conditioning A7 Certification Exam.